Musical notation - Clemons, Lorena Estella (My University, 1894)
Introduction: Musical notation of interest for the light which it throws upon music as for its own value. History of musical notation divided into three parts; first used being the letters of the alphabet; next sciatic characters, and last, we have the notes written on the lines and spaces of the staff. The different forms of staves used with the various systems of notation. The invention of the Time table. The value of notes fixed. Modification of measured music by mode, time, and probation, besides by position and rhythm. The division of the diatonic scale into the authentic and Plagal modes, each mode divided into Dominant, Mediant, and Participant. The sharp, flat, and natural and when first used. The change of musical typography in the form of notes. Marks of Expression; Major and minor scales. Value and forms of notes – measure, time signature, accent, tie, slur, syncopation, melody and stamony, the Tone Soh-fah-a system which requires no staff, where invented, Solfeggio. Conclusion.
Citation: Clemons, Lorena Estella. Musical notation. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Music; Notation; Composition; Theses; Manuscripts (documents)